Legal Construction in Indonesia's Right to Economic Self-Determination (RESD) of the Bilateral Investment Treaty (BIT) - Rahman, Irsan; Khuan, Hendri; Riana, Ana; Sari, Patma; Hidaya, Wahab Aznul; Nurikah, Nurikah (Faculty of Law, Universitas Pekalongan, 2024)
The study employs descriptive-analytical methods to examine the relevant laws and enforcement practices. It views the RESD as an emerging norm through a constructivist lens, influencing both the host countries and the global normative framework. The research finds a growing momentum to revise BIT clauses to better reflect dynamic RESD principles and social responsibility. This involves moving away from focusing solely on unilateral power. The study proposes a new model for RESD, aimed at promoting good governance and fairness in administrative processes. This model will be vital for renegotiating or redesigning BIT provisions, particularly for countries like Indonesia. By explaining the acronyms and simplifying the sentences, the key points become clearer: the need for a balanced approach in BIT negotiations, the role of RESD in this balance, and the potential for revised treaty clauses to better align with principles of social justice and fairness.